Approximation by algebraic numbers - Bugeaud, Yann, 1971- (Cambridge tracts in mathematics, 2004)
An accessible and broad account of the approximation and classification of real numbers suited for graduate courses on Diophantine approximation (some 40 exercises are supplied), or as an introduction for non-experts. Specialists will appreciate the collection of over 50 open problems and the comprehensive list of more than 600 references.